2022
DOI: 10.3390/ijerph192316254
|View full text |Cite
|
Sign up to set email alerts
|

Evacuation in Buildings Based on BIM: Taking a Fire in a University Library as an Example

Abstract: As a typical public place, a university library has a large collection of books with heavy fire load, dense population, and large flow of people. The situation of safe evacuation in case of fire is very serious. This study utilizes Revit, Pyrosim, and Pathfinder software to research evacuation of a university library. First, a Building Information Modeling (BIM) is constructed based on Revit software in 1:1 scale. Second, the evacuation passage with the highest utilization rate was determined through Pathfinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Evacuation routes should be clearly marked on walls and doors on each floor. Emergency exits and emergency exit indication signs should be added, and, to combat low visibility due to smoke, sound signals should be turned on to guide the evacuation [44]. Improving the safety awareness and knowledge of all personnel, broadcasting videos of relevant accidents and safety training for display on screens around the building, and regularly training and evaluating student safety and psychological knowledge, while ranking them, could also be beneficial.…”
Section: Proposed Fire Prevention and Evacuation Measuresmentioning
confidence: 99%
“…Evacuation routes should be clearly marked on walls and doors on each floor. Emergency exits and emergency exit indication signs should be added, and, to combat low visibility due to smoke, sound signals should be turned on to guide the evacuation [44]. Improving the safety awareness and knowledge of all personnel, broadcasting videos of relevant accidents and safety training for display on screens around the building, and regularly training and evaluating student safety and psychological knowledge, while ranking them, could also be beneficial.…”
Section: Proposed Fire Prevention and Evacuation Measuresmentioning
confidence: 99%
“…This framework was structured around four phases: initial preparation, optimization with a meta-heuristic algorithm, decision-making considering budget constraints, and applying selected measures into BIM. Another study used BIM tools such as Revit, Pyrosim, and Pathfinder software that highlighted the process of constructing a BIM in 1: 1 scale, determining the evacuation passage with the highest utilization, and simulating fire scenarios to assess smoke spread and evacuation conditions (Zheng et al, 2022). The study found that strategic man-made route planning could significantly improve evacuation efficiency by 13.67%, suggesting that similar strategies could be applied to hospital settings to optimize the layout of operating rooms and evacuation routes, thereby enhancing overall safety during emergencies.…”
Section: Building Information Modeling (Bim)mentioning
confidence: 99%
“…Effective evacuation guidance and layout can improve the efficiency of personnel evacuation and ensure their safety [15]. For example, Haotian Zheng et al [16] used Revit software to create a 1:1 scale BIM model and then used Pathfinder software to determine the most efficient evacuation channels. Following the "worst-case principle," they assumed that the nearby area was the location of a fire.…”
Section: Enhancing the Rationality Of Evacuation Routesmentioning
confidence: 99%